FEEDBACK OF THE SESSION ON PROFESSIONALISM AND ETHICS USING VARIOUS TEACHING METHODS AMONG UNDERGRADUATE MEDICAL STUDENTS - ARUNNAIR, VIJAYAMATHY; S, VELARUL; S, BHUVANESHWARI; MS, UMAMAGESWARI; VINOTHA AT, SATHIYA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: This study aims to assess the feedback of the session on professionalism and ethics using various teaching-learning (TL) methods among the 1st year undergraduate medical students. Methods: This was a cross-sectional study conducted among one hundred and twenty-four 1st year undergraduate medical students (2019–2020 batch) divided into three batches. They attended a 3 h session each day on professionalism and ethics module one using various TL methods such as an interactive lecture, a role play, and group discussion for 3 consecutive days. At the end of the session, the students filled out a self-administered questionnaire in a “Likert scale” design carrying a minimum score of 1 (1=strongly disagree) and a maximum score of 5 (5=strongly agree). Feedback was obtained to assess the quality of teaching and effectiveness of teaching methodologies. Descriptive statistics were used and the statistical analysis was performed using SPSS version 24. Results: Overall 93% of the students gave positive feedback on various domains of the session that included organization, presentation, rapport, credibility, and control. About 83% of students responded that various methods of teaching such as interactive lectures and role play were used. Conclusion: The majority of the students showed positive acceptance toward all aspects of this session. Active feedback given by the students may help us to identify the components that need to be upgraded for better delivery of course contents in the future.